Decoding the Dollars: How Much Does AI Medical Diagnosis Truly Cost? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Decoding the Dollars: How Much Does AI Medical Diagnosis Truly Cost? Keywords: AI medical diagnosis cost, economics of AI in healthcare, cost-effectiven...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care